Tutors as mediators of exchange student experiences: evaluation of the international student tutor system at the University of Turku - Siltanen, Henna (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
As academic student mobility is increasing, improving the functionality of international operations is recognised as a competitive advantage at tertiary education institutions. Although many scholars have researched the experiences of exchange students, the role of student tutors and their contribution to exchange students’ experiences is still an unknown factor. This research examines international tutoring at the University of Turku, and aims to understand better the way tutoring contributes to exchange experiences and to explore the functionality of the tutor system and discover areas for improvements. To achieve these goals, the research seeks to answer the fundamental research question: What is the role of tutors in mediating exchange experiences? The theoretical framework combines literature on mediating exchange experiences, the phenomenon of studying abroad, the process of adaptation, the importance of cross-cultural communication, and the role of student tutors as mediators. Based on the literature review, a theoretical model for studying the mediation of exchange experiences is introduced. The model’s applicability and validity is examined through a case study. Three methods were used in the empirical research: surveys, participant observations, and interviews. These methods provided extensive data from three major parties of the tutor system: tutors, exchange students, and the international office. The findings of the research reveal that tutoring – instrumental leading and social and cultural mediating – generates both negative and positive experiences depending on the individuals’ expectations, motivations, relationships, and the nature of the tutoring. Although functional, there are a few weaknesses in the tutor system. Tutors tend to act as effective instrumental leaders, but often fail to create a friendship and contribute to the exchange students’ experience through social and cultural mediation, which is significantly more important in the exchange students’ overall experience in terms of building networks, adapting, gaining emotional experiences, and achieving the stage of personal development and mental change. Based on the weaknesses, three improvements are suggested: (1) increasing comprehensive sharing of information, effective communication, and collective cooperation, (2) emphasising the importance of social and cultural mediation and increasing the frequency of interaction between tutors and exchange students, and (3) improving the recruitment and training, revising the process of reporting and rewarding, and finally, enhancing services and coordination.